Faktor-Faktor Yang Mempengaruhi Pemilihan Premis Makanan Dalam Kalangan Melayu Muslim Bandar: Satu Sorotan Literatur: Factors that Influence Food Premise Selection Among Urban Malay Muslims: A Literature Review - Kamarudin, Hazwani; Pauzi, Norhidayah; Man, Saadan; Syed Jaafar, Syed Mohd Jeffri (Jurnal Fiqh, 2020)
Based on the State of the Global Islamic Economy Report 2018/19, Malaysia is a pioneer in establishing a world-leading Islamic economy. Much research has been conducted on the awareness, understanding, behavior and choosing of halal foods among Muslims for several years. However, many issues regarding halal foods are still unresolved. It is viral in the social and electronics media about the misuse of the halal logo, cleanliness of the food premises, misunderstandings on halal food premises and ‘viral’ foods. As customers play a vital role in determining the development of the halal industry, this study identifies and analyzes several factors that influence the choice of food premises among urban Malay Muslims. Data collection is done by the method of documentation and which is then analyzed through inductive analysis. The findings show that many factors come into play when customers purchase food on the premises such as attitudes, subjective norms, perceived behavioral control, religiosity, the halal certificate and logo, demographic factors, culture, service quality at food premises and food attributes. Therefore, based on this library study, it is hoped that the selection of food premises among urban Malay Muslims would be continuously researched upon.